Desigualdades regionais do crescimento Industrial do Estado do Paraná - Claudio Roberto Bragueto; Luís Enrique da Silva (Confins)
The industrialization process of the Paraná State territory was slow, discontinuous and unequal. An analysis of the industrial characteristics of the state regions shows industrial differences and disparities. Therefore, the objective of this work is to analyze the territorial inequalities of the State of Paraná’s industrial growth between 1990 and 2013. In addition to the historical processes, more recently, in a period of reorganization of the industrial production process, the State of Paraná industry regional inequalities are connected with the differences in the production general conditions found in these regions. This turned them more or less attractive to capital as well as to the policy of investment attraction led by the Paraná State government. The database from the Ministry of Employment and Labor (RAIS – Annual Social Information Report) and statistical data collected by IPARDES (Institute for the Economic and Social Development of Paraná) served as main sources of information for this study. Results show that the historically established production general conditions and the investment attraction policy of the State government resulted in a polarized industrial development among the state’s regions. It is important to highlight that the industry of greater technological intensity has increased its concentration on the Metropolitan region of Curitiba while the industry with less technological intensity are more spatially dispersed, but concentrated on a few Mesoregions.